Ketahanan Keluarga Perspektif Maslahah Mursalah dan Hukum Perkawinan di Indonesia - Feni Arifiani (SALAM: Jurnal Sosial dan Budaya Syar-i, 2021)
AbstractFamily resilience is currently a top priority for state initiatives that address a variety of factors that contribute to family resilience, including physical, social, and psychological aspects. Several aspects of the Marriage Law, however, are in the spotlight because they are contentious. "Every husband and wife who are legally married have the duty to love, support, and preserve honor for each other." be faithful, and provide physical and spiritual assistance to one another." The rules on feelings suggest that a married couple must communicate their feelings to one another, and this is not without reason. The four advantages of sharing feelings of love include minimizing tension caused by pent-up emotions, making it easier for couples to understand each other, and making it easier for couples to communicate with each other. Being an efficient method on occasion. Marriage, according to the Marriage Law, is a sacred relationship created by a man and a woman as husband and wife in order to form a happy and everlasting family (household) founded on Almighty divinity. A family will be created as a result of this union. Many people believe that Family Resilience is a plagiarized version of the Islamic Law Compilation (KHI), "Both husband and wife are bound by the statute." to love, respect, and aid one another from one body to another. As a consequence, what some people are referring to is an article that already exists in the Marriage Law and KHI, which has existed in previous regulations and has never been challenged. AbstrakKetahanan keluarga yang saat ini menjadi prioritas program negara yang mencakup berbagai aspek yang dibutuhkan untuk memenuhi ketahanan keluarga, seperti aspek ketahanan fisik, sosial, dan psikologis. Namun beberapa hal dalam UU Perkawinan yang menjadi sorotan karena memicu kontroversi. “Setiap suami dan istri yang terikat dalam perkawinan yang sah berkewajiban untuk mencintai, menghormati, menjaga kehormatan, setia, dan saling memberikan bantuan jasmani dan rohani”. Aturan tentang perasaan menunjukkan perlunya pasangan suami istri untuk saling mengungkapkan perasaannya, tentunya hal ini bukan tanpa alasan. Empat manfaat dalam mengungkapkan perasaan cinta antara lain mengurangi stres akibat terpendam, memudahkan pasangan untuk saling memahami, terkadang menjadi cara yang efektif. UU Perkawinan mendefinisikan pernikahan sebagai ikatan spiritual antara laki-laki dan perempuan sebagai suami istri untuk membentuk keluarga (rumah tangga) yang bahagia dan abadi berdasarkan ketuhanan Yang Maha Kuasa. Dari pernikahan ini akan terbentuk sebuah keluarga. Ketahanan Keluarga yang dipermasalahkan oleh banyak orang merupakan penjiplakan dari Kompilasi Hukum Islam (KHI), “Suami istri wajib hukumnya. untuk saling mencintai dalam cinta, menghormati dan memberi bantuan dari satu tubuh ke tubuh lainnya. Dengan demikian yang dimaksud oleh sebagian orang tersebut merupakan pasal yang sudah ada dalam UU Perkawinan dan KHI, dimana sudah ada pada peraturan sebelumnya dan tidak dipersoalkan sampai sekarang.